Edukasi Kebutuhan Serat Terhadap Kejadian Konstipasi pada Lansia Di Wilayah Kerja Puskemas Lempake Kota Samarinda - Iskandar Muda; Iskandar, Abdillah; Bahtiar; Khumaidi; Metungku, Fanny; Hastati, Sri; Yuniati (Fakultas Kedokteran, Universitas Mulawarman, 2024)
Engaging in community service involves educating people about the importance of fiber in relation to constipation in the elderly, which is frequently brought on by modifications in the body's physiological processes. The purpose of the community service is to raise awareness of the role that fiber plays in reducing the prevalence of constipation in the elderly. Fifteen elderly participated in this activity at the Baitul Maghfirah Lempake Mosque on August 20, 2023. The educational initiatives included the distribution of materials emphasizing the importance of fiber in relation to the prevalence of constipation among the elderly. The elderly's increased knowledge, as evidenced by their ability to respond to the questions posed by the younger people, was one way that this activity improved the community atmosphere.